(untitled) (Journal of Academic Research, 2021)
There is a direct relationship between the verses of the Quran with many subjects and modern scientific terms. The holy Quran came with high precision linguistic styles that never and will not be brought about by humans. The study aims at identifying certain direct or indirect terminologies specific for weather and climate, whether they may or may not be used in the daily life that were that mentioned in the holy Quran and to compare them with the used modern terms to determine how these terms match or differ among each other. The study also examines the reason for the difference in the used terms in the meteorological authority between the Arabic language, the holy Quran and scientific references. The research also studies the recent discoveries for weather and climate that were mentioned in the holy Quran 1400 years ago. The study concludes with certain results and recommendations.